Improved Performance of Airfoils Through Vortex Generators Flow Control - Oyewola, Olanrewaju Miracle; Armstrong, Alex; Johnson, Matthew; Piltz, Gordon; Richards, Wyatt (European Journal of Applied Sciences, 2026)
Commercial airliners are an irreplaceable aspect of modern society with 4.1 billion passengers per year on 37 million flights. Commercial flights are integral to not only passenger transportation but also to transportation of freight.[4] According to the Air Transport Action Group using air transportation significantly impacts the environment. In 2019, the global aviation industry accounted for 2.1% of all human carbon dioxide emissions and 12% of all transportation carbon dioxide emissions [5]. To increase the efficiency of commercial flights, optimizations can be made in subsonic or transonic regimes via flow control. In this work “Smart” Vortex generators, which only are active at low altitudes, were explored for subsonic flow using CFD. It is found that climbing performance is increased. In addition, while the plane's lift is triple, flow separations is reduced at a free stream velocity of 150 mph and at an angle of attack of 8. The overall result suggests the effectiveness of vortex generators as a flow control mechanism especially at a subsonic flow regime. It is however recommended that a combination of flow control strategies over a range of flow regimes will be of great advantage taking into consideration the gains from individual control mechanism.